Empowerment of Community Self-Help Groups (KSM) in Maggot Cultivation to Support the Economy in Pudak Village, Muaro Jambi Regency in 2024 - Erris, Erris; Ariyadi, Bambang; Harahap, V.A Irmayanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This method is considered to provide the greatest benefits and is relatively easy to implement. One of them is by empowering the community through Community Self-Help Groups (KSM) in managing organic waste. Maggots or maggots are the larvae of the Black Soldier Fly (Hermetia Illucens, Stratimydae, Diptera) which is a family of flies, but the size of the BSF, known as the soldier fly, is longer and larger. Even though it is from the fly family, BSF does not transmit bacteria, diseases or even germs to humans. Like maggots, ecologically maggots are useful in the process of decomposing organic materials. Maggots eat vegetable and fruit waste, therefore maggots are very suitable for use in organic waste management. Even though it is made from organic waste, the fertilizer produced does not smell